2022
DOI: 10.20396/parc.v13i00.8667258
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho higrotérmico de paredes de alvenaria em edificação residencial em clima subtropical úmido

Abstract: A falta do controle da umidade em edificações pode afetar a durabilidade dos materiais, o conforto térmico, o consumo energético e a qualidade do ar interno, assim como propiciar o crescimento de micro-organismos (fungos filamentosos) prejudiciais à saúde do usuário. Nesse contexto, o objetivo deste estudo é analisar o comportamento higrotérmico de quatro configurações de sistemas de vedação vertical externa (SVVE) de tijolos cerâmicos com diferentes níveis do isolamento térmico e estanqueidade à água para o c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Santos and Penteado Neto (2020) evaluated the houses' pathologies during operational use, and most of the time, the problems came from concrete structure deformation and water pipe leakage. Buligon et al (2022) also showed that, in residential buildings in general, the conventional walls (such as concrete or ceramic brick) do not minimise moisture and have the potential for mould formation. There is also criticism about the absence of spaces for future expansion (Müller;Lima, 2017), and one may consider this need when designing new housing units.…”
Section: Introductionmentioning
confidence: 99%
“…Santos and Penteado Neto (2020) evaluated the houses' pathologies during operational use, and most of the time, the problems came from concrete structure deformation and water pipe leakage. Buligon et al (2022) also showed that, in residential buildings in general, the conventional walls (such as concrete or ceramic brick) do not minimise moisture and have the potential for mould formation. There is also criticism about the absence of spaces for future expansion (Müller;Lima, 2017), and one may consider this need when designing new housing units.…”
Section: Introductionmentioning
confidence: 99%